Antiviral activity of eicosapentaenoic acid against zika virus and other enveloped viruses - Feng, Yifei; Qiu, Shuqi; Zou, Shuting; Li, Ru; Chen, Hongyu; Chen, Kaitian; Ma, Junbo; Liu, Jinyu; Lai, Xiaoyun; Liu, Shuwen; Zou, Min (Frontiers in Pharmacology, 2025)
BackgroundZika virus (ZIKV) is an emerging flavivirus that may cause innate microcephaly or neurological disturbances. Yet no antiviral has been approved by FDA against ZIKV infection. It was shown that some unsaturated fatty acids could inactivate enveloped viruses including SARS-CoV-2. However, studies investigating the effect of eicosapentaenoic acid (EPA) on ZIKV infection are lacking. This study aims to evaluate the antiviral effect of EPA against ZIKV and other enveloped viruses.MethodsWe first explored the toxicities of EPA in vitro and in vivo. Then we examined the antiviral effect of EPA against ZIKV via cell-based immunodetection, qRT-PCR, Western blotting, and so on. To uncover its antiviral mechanism, we performed assays for virus binding, adsorption and entry, and time-of-addition. RNase digestion and ZIKV NS2B-NS3 protease inhibition assays were also adopted. Finally, we detected its effects on dengue virus (DENV)-2, herpes simplex virus (HSV)-1 and influenza A virus via MTT, Western blotting and qRT-PCR assays.ResultsEPA was found to inhibit ZIKV infection in vitro without causing cytotoxicities. EPA exhibited antiviral activity in the early stages of the ZIKV life cycle quickly. Mechanistic experiments showed that EPA disrupted the membrane integrity of viral particles, leading to the release of viral RNA, together with the interruption of ZIKV from binding, adsorption and entry, and ultimately the inhibition of viral proliferation. Furthermore, EPA exerted antiviral effects against DENV-2, HSV-1, and influenza virus, in a dose-dependent manner.ConclusionThese findings suggest that EPA is a promising broad-spectrum antiviral drug candidate.